The Importance Of Fulfillment Of Parenting Patterns And Learning Culture In Pp Muhamadiyah, In Meri Village, Mojokerto - Solichah; Dwi Dewianawati; Erry Setiawan (International Journal Of Community Service, 2021)
Community service is carried out at PP Muhammadiyah Putri, Meri village, Mojokerto, with the aim of: 1) Supporting and strengthening the Covid-19 countermeasures and prevention programs carried out by the central and local governments. 2) Increasing the level of concern for Unimas academic citivity in accelerating prevention, transmission of Covit -19, 3) Lighten the burden on the community affected by covid -19. Problems faced 1) Low school achievement of children who are left behind in PP Muhammidiyah Putri, 2) Low interest in learning children living in PP Muhammadiya Putri, 3). Less conducive learning environment, the method used in lectures and discussions. Programs implemented are 1) Child Development through Learning Culture, 2) Community Service, 3) Social Service, implemented smoothly as expected. Participants in the activity responded positively and expressed their gratitude to the academic activities of Unimas for providing useful knowledge to participants, namely fostering interest in learning to increase achievement, therefore hope that there is a continuation of the activity and it does not stop here.